Virtual reality's effects on air crash accident investigation learning interaction - Faisal Othman H Alburaidi; Karl Jenkins; Tom-Robin Teschner (Computer Science and Information Technologies, 2023)
The objective of this study is to gain a deeper comprehension of the factors that play a role in the evolution of virtual reality (VR) for application in the investigation of aviation disasters. This study was motivated by the concept of utilising VR to create an illusion of the procedures involved in an anviation accident. A conceptual model has been presented, to create the scene that will be simple to understand the procedure of accident following an air crash. The idea is to compile a series of steps that an investigation team will go through and then present them in VR. This stage entails obtaining complete views of the object before it crashes and at ground level. This study contributes to the process of creating the groundwork for adopting VR in air crash investigations to provide instructional experiences. The idea that was presented in this research focuses on feature of the surrounding area of the crash or accident, wreckage distribution, wreckage above the ground, wreckage in motion, wreckage at the ground, spatial view effect, and full view projection as the primary VR features that are required for teaching and learning about air crash accident investigations using VR.